PENGEMBANGAN SISTEM INFORMASI WEB CAFE HAGI DENGAN METODE CUSTOMER RELATIONSHIP MANAGEMENT - Maria Sri Wulandari; Rahayu Noveandini; Rivaldi Rahman (Journal of Information System, Informatics and Computing, 2026)
The development of information technology is driving transformation in business processes, particularly in transaction and data management. Cafe Hagi currently still implements a cash payment system that limits transaction flexibility for customers. The design in this study aims to build a web-based sales system integrated with a payment gateway and Customer Relationship Management (CRM) features to improve operational efficiency and quality service. The system development method selected uses the Software Development Life Cycle (SDLC) with the Waterfall model. The development stages consist of planning, requirements analysis, design using UML with implementation, and system testing. Web technology is the choice for system development, supported by a relational database and integrated digital payment services and message notifications. The results of the study indicate that the system is able to support non-cash transactions, simplify sales data management, and enhance interaction with customers through CRM features. Thus, this system has the potential to improve operational effectiveness and business competitiveness in the face of digital developments..The research results indicate that the developed system is capable of supporting non-cash transactions, simplifying sales data management, and enhancing customer interaction through CRM features. Therefore, this system has the potential to improve operational effectiveness and business competitiveness in the face of digital developments.